The Role of Technology Information on Financial Literacy in Indonesia - Rizkan, Muhammad; Hartarto, Romi Bhakti; Supiandi, Supiandi; Hou, Chieh-Tse (Jurnal Ekonomi & Studi Pembangunan, 2022)
Financial management literacy is a significant knowledge to assist individuals' financial condition. There are various factors influencing monetary management, including Information technology (IT). Thus, this study aims to investigate the role of IT affecting individual awareness of financial literacy in Indonesia with household characteristics as the controlling variable; the data are generated from the Indonesian Family Life Survey conducted in 2014. Probit and logit models signify that ITs and household characteristics positively and significantly affect financial literacy. In detail, handphones, televisions and newspapers, marital status, education level, and household income levels have a positive and significant influence on households' accessing financial knowledge. Furthermore, multinomial logit estimation used to compare three different levels of financial literacy (low, medium, and high), indicates that six out of nine variables significantly affect financial literacy at low level to high levels, whereas only four out of nine influence financial literacy from medium to a high level.